Acute Kidney Injury and Intestinal Dysbiosis - Chávez-Iñiguez, Jonathan Samuel; Villegas-Gutiérrez, Luz Yareli; Gallardo-González, Alejandro Martínez (Frontiers in Nephrology, 2022)
Within the multiple communication pathways of the intestine-kidney axis, one of the most important pathways is the interaction between the commensals of the intestinal microbiome, through the production of short-chain fatty acids, and the segments of the nephron. These interactions maintain a perfect environmental balance. During AKI, there are negative repercussions in all organs, and the systemic interconnection is related in part to the intense inflammation and the uremic environment that this syndrome generates. For example, in the intestine, the microbiome is severely affected, with a decrease in benign bacteria that promote anti-inflammatory effects and an increase in negative, pro-inflammatory bacteria. This scenario of intestinal dysbiosis widens the inflammatory loop that favors worsening kidney function and the probability of dying. It is possible that the manipulation of the intestinal microbiome with probiotics, prebiotics and symbiotics is a reasonable therapeutic goal for AKI.